Image Enhancement using Fuzzy Inference System - Venkateshwarlu, K. (My University, 2010)
Present day applications require various kinds of images and pictures as sources of information for interpretation and analysis. Whenever an image is converted from one form to another such as, digitizing, scanning, transmitting, storing, etc., some of the degradation occurs at the output. Hence, the output image has to undergo a process called image enhancement which consists of a collection of techniques that seek to improve the visual appearance of an image. Image enhancement is basically improving the interpretability or perception of information in images for human viewers and providing 'better' input for other automated image processing techniques. The fuzzy set theory is incorporated to handle uncertainties (arising from deficiencies of information available from situation like the darkness may result from incomplete, imprecise, and not fully reliable, vague). The fuzzy logic provides a mathematical frame work for representation and processing of expert knowledge. The concept of if-then rules plays a role in approximation of the variables likes cross over point. Also the Uncertainties within image processing tasks are not always due to randomness but often due to vagueness and ambiguity. A fuzzy technique enables us to manage these problems effectively. Fuzzy inference system is the process of formulating the mapping from a given input to an output using fuzzy logic. The process of fuzzy inference involves all of the pieces that are: Membership Functions, Logical Operations, and If-Then Rules. In this thesis work a technique is designed based on Fuzzy Inference System tool in MATLAB 7.5 (MATLAB is a software package developed by Math Works). The proposed technique used fuzzy if – then rules are a sophisticated bridge between human knowledge on the one side and the numerical framework of the computers on the other side, simple and easy to understand. The proposed technique is able to improve the contrast of the image. In this thesis work an algorithm is proposed and implemented to enhance image using fuzzy technique. This algorithm is used to convert the image properties into fuzzy data and fuzzy data into defuzzification.
ME
Keywords: Fuzzy; Image Enhancement